END OF FOSSIL DEPENDENCY – “REPOWEREU” PLAN - Kanapiyanova, Zh. (Farabi Journal of Social Sciences, 2023)
The European Commission presented the “REPowerEU” plan, the response to the Russian invasion of Ukraine, and the disruption of the global energy market. There are two important reasons for transforming Europe’s energy system. The first is to end the European Union’s (EU) dependency on Russian fossil fuels, which are used as an economic and political weapon and cost European taxpayers billions of euros a year, while the second is to tackle the climate crisis. The majority of Europeans believe that the EU should reduce its dependence on Russian gas and oil as soon as possible to support Ukraine. In this context, the “RePowerEU” plan can respond to this goal by saving energy, diversifying energy sources, and accelerating renewable energy to replace fossil fuels in homes, industry, and electricity generation. The aim of the study is to investigate the RePowerEU plan for reducing the EU’s dependence on Russian fossil fuels and supporting green energy and revealing its pros and cons. The background of the study was analyzed within the framework of the theory of interdependence. According to the results of the study, the pros and cons of the plan were determined and it was tried to predict to what extent the EU’s dependence on Russian fossil fuels would decrease. The study is expected to contribute to the literature in the context of using and analyzing Western and Russian sources together. Keywords: European Union, energy, dependency, RePowerEU, Russia.